2016
DOI: 10.1007/s11145-016-9694-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of schools: teacher knowledge of explicit code-based reading instruction

Abstract: Nancy: We have known each other for a long time, so it seems only fitting for you to see me through to the end. I appreciate your expertise, guidance, and valuable (and always timely!) feedback. I am grateful for your keen insight into my chosen dissertation topic. While I wanted to write a dissertation that would revolutionize the special education world, you steered me toward just changing a little, yet important, piece-for now. June: My editor extraordinaire, you helped me publish a paper I am proud to say … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Findings from Stark et al (2015) echo earlier studies of Australian teachers (Fielding-Barnsley and Purdie, 2005;Mahar and Richdale, 2008) and international teachers' (e.g. Arrow et al, 2019;Bos et al, 2001;Cohen et al, 2017) incomplete knowledge about linguistic constructs that are considered critical for teaching reading competently. Importantly, Stark et al (2015) identified no significant relationship between teachers' perceived knowledge about language and linguistic constructs and their actual performance on the questionnaire.…”
Section: Discussionsupporting
confidence: 73%
“…Findings from Stark et al (2015) echo earlier studies of Australian teachers (Fielding-Barnsley and Purdie, 2005;Mahar and Richdale, 2008) and international teachers' (e.g. Arrow et al, 2019;Bos et al, 2001;Cohen et al, 2017) incomplete knowledge about linguistic constructs that are considered critical for teaching reading competently. Importantly, Stark et al (2015) identified no significant relationship between teachers' perceived knowledge about language and linguistic constructs and their actual performance on the questionnaire.…”
Section: Discussionsupporting
confidence: 73%
“…Professional training must reach schools who do not know what they do not know: the problems associated with limited meta‐knowledge in weaker schools are well documented (OfSTED, 2012). The thinking that pupil characteristics can of themselves be blamed for poor outcomes may well have been related to teachers' own false confidence in their limited subject knowledge (Cohen, Mather, Schneider, & White, 2017; Joshi et al, 2009; Stark et al, 2016) and this suggests a persisting problem, albeit with a minority of practitioners. Moreover, lack of any reference to teaching phonics in KS2 in the follow‐up data demonstrates there is still a need to upskill all primary school professionals in the teaching of phonics.…”
Section: Discussionmentioning
confidence: 99%
“…Spear Swerling and Cheesman (2012) found that teachers dem onstrated more difficulty in applying knowledge (e.g., giving appropriate examples, recognizing when text is too difficult to decode, understanding the interpretation of assessments) than correctly answering items that assessed content knowledge. Moreover, providing teachers with well designed materials does not correct these misunder standings (R.A. Cohen, Mather, Schneider, & White, 2017). In other words, a well designed curriculum cannot replace a knowledgeable teacher who understands the science of reading and how to use that knowledge to plan for effective literacy instruction (Bembry, Jordan, Gomez, Anderson, & Mendro, 1998;Snow, Barnes, Chandler, Goodman, & Hemphill, 1991).…”
Section: Teacher Knowledgementioning
confidence: 99%